Masculinities in Transit: The Voices of Motorcyclists - Johanna Burbano-Valente; Martin Emilio Gafaro-Barrera; Angelica Paola Torres-Quintero; María Teresa Dominguez-Torres (Masculinities and Social Change, 2019)
This paper reports on the construction of masculinities in the narratives of 11 motorcyclists in Valledupar – Colombia. The aim was to establish the ways masculinities are expressed and recreated by motorcycle riders and the importance of motorcycles in these expressions. To do this, semistructured interviews were conducted to search for the evolution of their personal stories as men and on their relationship with motorcycles. We found that their masculinities are currently “in transit”: they vary from hegemonic manifestations to peripheral masculine ways of expression. Evidence of these transits can be grouped around four emerging categories: risk behavior, amusement settings, sexual expression and roles in public and private settings. Results show that, in some of these categories, the hegemonic patriarchal masculine logic prevails, especially through risky behaviors and motorcycle riding. However, other disruptive ways of expressing masculinities were found, motivated by the social transformations in equality policies, changes in interpersonal relationships and the participants’ own experiences. Supporting the transition process of masculinities is a large responsibility in social interventions seeking for a more equitable and fair society.